Axiological Approaches to Increase Students Social Activities - Abdullayeva, Kibriyo (Indonesian Journal Publisher, 2024)
This article discusses importance and advantages of social and national pedagogy in increasing students’ social activities. Also, physical education and sports are a healthy way of life that should become an integral part of everyday life which all the organs and systems in the human body is refreshed by physical activity or physical education and sports. Also the benefits of Uzbek national games are discussed in this article.